2009
DOI: 10.1159/000208790
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Plasma Separation and Adsorption Significantly Decreases Intracranial Pressure in Acute Liver Failure: Experimental Study

Abstract: Background: The aim of the study was to determine the influence of fractionated plasma separation and absorption (FPSA) on intracranial pressure (ICP) in acute liver failure (ALF). Methods: A surgical model of ALF in pigs (35–40 kg) was used. We compared laboratory data and haemodynamic parameters from the ALF control group to the ALF group treated by Prometheus using ANOVA with repeated measures and grouping factors, by calculating the area under the curve, and by the Mann-Whitney rank test. Results: Bilirubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
(29 reference statements)
2
6
0
1
Order By: Relevance
“…The rise in ICP observed in the FPSA group, even if it was significantly less than the ALF group, suggests a multiple causes for the intracranial hypertension associated with ALF [14], which can only be partially ameliorated by the supporting toxin-eliminating method. Our findings support the conclusions of previous studies and confirm the efficacy of toxin elimination in as a treatment for intracranial hypertension in ALF [3] . The most significant difference between the ICP measured in the FPSA and control groups was observed 9 hours after surgery (7 hours after initiation of FPSA therapy).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The rise in ICP observed in the FPSA group, even if it was significantly less than the ALF group, suggests a multiple causes for the intracranial hypertension associated with ALF [14], which can only be partially ameliorated by the supporting toxin-eliminating method. Our findings support the conclusions of previous studies and confirm the efficacy of toxin elimination in as a treatment for intracranial hypertension in ALF [3] . The most significant difference between the ICP measured in the FPSA and control groups was observed 9 hours after surgery (7 hours after initiation of FPSA therapy).…”
Section: Discussionsupporting
confidence: 93%
“…A variety of approaches may be taken to meet homeostatic needs during the critical period when a donor organ is sought (bridging therapy). Supportive therapy using fractionated plasma separation and adsorption (FPSA) appears to have a beneficial effect on intracranial hypertension [3]. The efficacy of FPSA therapy in treatment of ALF-related brain injury is usually monitored by measuring ICP.…”
Section: Introductionmentioning
confidence: 99%
“…These more pronounced effects on cerebral perfusion pressure are supported by elimination of ammonia by Hepa Wash. In the animal studies on MARS and Prometheus [21,22], the intracranial pressure was significantly reduced, though no significant elimination of ammonia was found. The lower levels of intracranial pressure in our ALF model compared with the other models and the resultant difficulty in showing significant differences may explain the different results.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated a decrease in intracranial pressure after treatment with FPSA [14]. A favorable shift in the amino acid profile toward branched chain amino acids, reduction in plasma ammonia levels and oxygen saturation of jugular venous bulb blood (SjVO 2 ) have also been reported [15,16].…”
Section: Hepatic Encephalopathy In Aclfmentioning
confidence: 98%